Optimizing the Potential of Zakat Management in Indonesia Through Technology Integration - Asytuti, Rinda; Fathul Arifin; Khalimi Shubhi (Journal Of Islamic Economics And Finance, 2025)
Zakat has significant potential in improving the welfare of individuals and communities in Indonesia. As a pillar of Islamic finance, zakat is the obligatory act of giving a certain portion of one's wealth to support the less fortunate. The purpose of this study is to provide a comprehensive understanding to policymakers, zakat institutions, and stakeholders about potential challenges and solutions for effective zakat management in Indonesia. The method used in this research is the literature study method or commonly referred to as literature review or secondary research. Effective zakat management in Indonesia can be significantly improved by integrating technological elements, such as digital platforms. Digital media offers a convenient and secure zakat payment system, increasing efficiency and expanding participation.